The Identification of Significant Features Towards Tourist Visits Intention: A Focus on Concert Events in Saudi Arabia - Alatawy, Khald (مجلة العلوم الإدارية و الإقتصادية, 2025)
The purpose of this research was to investigate visitors’ intention to visit the Kingdom of Saudi Arabia specifically for concert events. A quantitative research approach was employed to collect and analyze data in order to gain insights into this phenomenon. The study collected a sample of 384 individuals from both local and international tourists in Saudi Arabia using a convenience-sampling technique. The collected data was analyzed using SPSS (Statistical Package for the Social Sciences) and PLS-SEM (Partial Least Squares Structural Equation Modeling) with the assistance of Smart-PLS 3.3.9 software. The findings of the study indicate that visitors’ attitude, subjective norms, e-word of mouth, and destination image have direct and positive impacts on their intention to attend concert events in Saudi Arabia. Moreover, the research revealed that past travel experience plays a significant moderating role in the relationships between e-word of mouth and visitors’ intention, as well as between destination image and visitors’ intention. However, past travel experience was not found to have a significant moderating effect on the relationship between attitude and visitors’ intention, nor on the relationship between subjective norms and visitors’ intention. The results of this study have implications for policy makers, the Saudi Arabian government, the Saudi tourism industry, researchers, and other stakeholders. They can utilize these findings to enhance their understanding of visitors’ intentions regarding concert events in Saudi Arabia and to develop effective strategies to promote such events. It is important to acknowledge certain limitations of this study. Firstly, the research relied solely on quantitative methodology, and cross-sectional data was analyzed, limiting the depth of insights that could be obtained. Future research could benefit from adopting a mixed methods approach and conducting longitudinal studies to gain a more comprehensive understanding of the subject.